AB0531 Anti-centromere positive primary sjÖgren's syndrome – challenge to classification criteria. (15th June 2017) - Palshina, S; Vasiliev, V; Sokol, E; Chaltsev, B; Rodionova, E; Safonova, T
Abstract : Background: The prevalence of anti-centromere antibodies (ACA) among patients with primary Sjögren's syndrome (pSS) varies from 3, 7% till 10, 9% [1;2]. They have special course of the disease: 1) with some features of systemic sclerosis (SSc), but rarely evolve to it, 2) higher prevalence of hepatitis and primary biliary cholangitis - PBC. Objectives: to describe the peculiarities of this subgroup; to evaluate it's conformity to the latest classification criteria for pSS (2012, 2016) [3;4] and prevalence of SSc with ACR2013 criteria [5]. Methods: From 2012 to 2016 in a single rheumatic center 50 ACA positive patients (47 female; 3 male) national (Russian) criteria (1987) and in 68%cases - AECG 2002 criteria for pSS (SSc excluded) [Tabl.1]. The mean age was 59, 2±9, 6 yrs. All diagnostics methods are listed in the table 1, lymphomas were verified pathomorphologicaly with immunohystochemical staining. Results: In our study 2/3 (64%) ACA+pts with pSS did't fulfill ACR2012 criteria, because of the lack of aRo or aLa or combination of RF+ANA. According to the criteria, 2016 [4] also just 60–68% pts will have ≥4scores for diagnosing pSS. SSc (limited form) due to new criteria [5] might be revealed in 11/50 (22%) cases. MALT lymphoma of salivary glands arised in 5/6 pts with visible enlargement of parotid glands. Conclusions: pSS with positive ACA is challenging for diagnostics with comprehensive classification criteria (32–64% doesn't meet it [3;4]). These patients overlaps SSc, some PBC. PBC is not rare among, but biliary tract lesions (AMA+(rarely absent, 2% in our study) with slightly elevated liver enzymes, esp.GGT, and stage 1 typical to PBC without progression) are more common. References: Bournia VK et al. Anticentromere antibody positive Sjögren's Syndrome: a retrospective descriptive analysis. Arthritis Res Ther. 2010;12(2): R47. Nakamura H et al. Anti-centromere antibody-seropositive Sjögren's syndrome differs from conventional subgroup in clinical and pathological study. BMC Musculoskelet Disord. 2010 Jul 1;11:140. Shiboski SC et al. American College of Rheumatology Classification Criteria for Sjögren's Syndrome: A Data-Driven, Expert Consensus Approach in the SICCA Cohort. Arthritis Care Res (Hoboken). 2012; 64(4): 475–487. Shiboski SC et al. 2016 American College of Rheumatology/European League Against Rheumatism Classification Criteria for Primary Sjögren's Syndrome. ARTHRITIS & RHEUMATOLOGY. 2016; Vol. 00 (00): p 00–00. van den Hoogen F et al. 2013 classification criteria for systemic sclerosis: an American College of Rheumatology/European League against Rheumatism collaborative initiative. Arthritis Rheum. 2013 Nov;65(11):2737–47. Disclosure of Interest: None declared